The Appropriation of Information and Communication Technologies by the Plymouth Brethren Christian Church - Knowles, Steven (The journal of CESNUR, 2021)
This article examines why the PBCC has adopted and adapted information and communication technologies (ICTs) in their community, given that until recently they have rejected them on theological grounds. Starting by tracing the attitudes of Brethren leaders toward emerging technologies such as the radio and television, I argue that the adoption and adaptation of technology has been necessary and fundamental in maintaining the integrity of the core belief in separation from the world, a doctrine central to the Brethren way of life. Using Silverstone et al.'s notion of the moral economy of the family in relation to how Brethren negotiate their way around ICTs, I conclude that without the reconstruction and cultural appropriation of ICTs the Brethren would not be able to maintain separation from wider society.